An innovative augmentation technique of savonius wind turbine performance. Issue 1 (February 2020) - Youssef, Khaled M; El Kholy, Ahmed M; Hamed, Ashraf M; Mahmoud, Nabil A; El Baz, Ahmed M; Mohamed, Tamer A
This work presents an innovative technique to enhance the performance of the Savonius wind turbine. The new technique is based on introducing an upstream deflector and downstream baffle. The shape and location of both devices are optimized using a genetic algorithm. The performance of the turbine with the optimized devices is compared with the single Savonius turbine performance. The study employs the finite volume solver (ANSYS-FLUENT) to solve unsteady Reynolds Averaged Navier–Stokes equations and turbulence model equations. The optimized configuration results in much higher power coefficient than the Savonius turbine. The average peak power coefficient using both deflector and baffle is 0.47 compared to 0.24 of the Savonius turbine. The peak power coefficient of the turbine corresponds to a speed ratio close to unity. This improved performance is attributed to the favorable aerodynamic interaction between the turbine and the downstream baffle which accelerates the flow around the rotor and generates larger turning torque. The baffle generates a jet effect on the advancing bucket and accelerates the flow behind the bucket creating a large zone of negative pressure and thereby increases the driving torque. Furthermore, the upstream deflector (also called shield or curtain) produces a shield for the returning bucket of the turbine which diminishes the adverse effect associated with the returning bucket on the aerodynamic torque of the turbine. This remarkable improvement of turbine performance will encourage the future application of the Savonius wind turbine in small power applications of wind energy.